The important roles of RET, VEGFR2 and the RAF/MEK/ERK pathway in cancer treatment with sorafenib - Mao Wei-feng; Shao Min-hua; Gao Pin-ting; Ma Ji; Li Hui-juan; Li Gai-ling; Han Bao-hui; Yuan Chong-gang (Acta Pharmacologica Sinica, 2016)
Aim: To elucidate the roles of receptor tyrosine kinases RET and VEGFR2 and the RAF/MEK/ERK signaling cascade in cancer treatment with sorafenib. Methods: The cell lines A549, HeLa, and HepG2 were tested. The enzyme activity was examined under cell-free conditions using 384-well microplate assays. Cell proliferation was evaluated using the Invitrogen Alarmar Blue assay. Gene expression was analyzed using the Invitrogen SYBR Green expression assays with a sequence detection system. Protein expression analysis was performed using Western blotting. Results: Sorafenib potently suppressed the activities of cRAF, VEGFR2, and RET with IC50 values of 20.9, 4 and 0.4 nmol/L, respectively. Sorafenib inhibited cRAF, VEGFR2, and RET via non-ATP-competitive, ATP-competitive and mixed-type modes, respectively. In contrast, sorafenib exerted only moderate cytotoxic effects on the proliferation of the 3 cell lines. The IC50 values for inhibition of A549, HeLa, and HepG2 cells were 8572, 4163, and 8338 nmol/L, respectively. In the 3 cell lines, sorafenib suppressed the cell proliferation mainly by blocking the MEK/ERK downstream pathway at the posttranscriptional level, which in turn regulated related gene expression via a feed-back mechanism. Conclusion: This study provides novel evidence that protein kinases RET and VEGFR2 play crucial roles in cancer treatment with sorafenib.